Tibial Derotational Osteotomy for Patellofemoral Instability: A Systematic Review - Phillip Wyatt; James Satalich; Zylyftar Gorica; Conor O’Neill; John Cyrus; Alexander Vap; Robert O’Connell (Advances in Orthopedics, 2022)
Introduction. The etiology of patellofemoral (PF) instability is multifactorial. Excessive external tibial torsion has been associated with recurrent patellar subluxation and persistent anterior knee pain. Several surgical techniques have been historically used to correct this, including medial patellofemoral ligament reconstruction, tibial tuberosity transfer (TTT), trochleoplasty, and tibial derotation osteotomy (TDO). The purpose of this systematic review is to investigate the safety and efficacy of TDO for PF instability and pain. Methods. A thorough search of the literature was conducted on July 15, 2022. Seven studies met the inclusion criteria for this systematic review. Results. Among the included studies, there were 179 total subjects and 204 operative knees. Mean follow-up time was 66.31 months (range 11–192). Complication rate was low (12.8%) in studies that reported complications. Average degree of anatomical correction in the transverse plane was 19.9 degrees with TDO. This increased to 34 degrees when combined with TTT. All PROMs assessed were significantly increased postoperatively (p<0.05). Age greater than 25 years and advanced PF chondromalacia may negatively affect postoperative outcomes. Conclusion. The primary findings of this review were as follows: (1) TDO results in significantly improved pain and PROM ratings in patients with PF pain and/or instability, (2) the likelihood of complication, including recurrent patella subluxation after TDO, is low but may be increased by aging, and (3) the successful anatomical correction of TDO may be augmented by concurrent TTT in some cases.